Leadership in SMEs: A Review of Different Leadership Styles and their Relevance to SME Management - Md. Manir Hossin; Professor Dr. Md. Shah Azam; Dr. Md. Shamim Hossain (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This review study was motivated by the premise that the relevance of leadership concepts to small and medium enterprises (SMEs) is a key factor to effective management. Because the use of an appropriate leadership style enables the SME management to move forward and to be successful in achieving organizational goals. This academic evaluation examines the concepts of leadership, leadership styles and their relevance towards the improvement of SME management. It begins with a concise overview of the meaning and concept of leadership and then follows with an examination of different leadership styles usually relevant to SME management. This study followed a qualitative research approach where secondary research data from previously published research articles, books, journals, conference papers, reports, and dissertations was integrated and interpreted. Based on the existing reliable literature, this review study validates that the identification and application of the most appropriate leadership style or the combination of leadership styles is highly important in achieving the common goal, which ultimately results in the SME's overall success.